EFFECTS OF grape powder SUPPLEMENTATION ON INFLAMMATION IN hemodialysis patients. - Alessandra GPR Janiques; Milena B Stockler-Pinto; Viviane O Leal; Nara X Moreira; Denise Mafra (The Korean Society of Nephrology, 2012)
Polyphenols and antioxidants anti-inflammatory have been considered pharmacological agents to combat oxidative stress in chronic diseases due the reduction in the formation of free radicals (FR). Hemodialysis (HD) patients have an imbalance between oxidant and antioxidant activity, with increased levels of FR and consequently an increase of lipid peroxidation, thereby raising the risk for cardiovascular disease (CVD). The beneficial health effects of grape juice or red wine for these patients have been attributed to the antioxidant activity of its polyphenols. Then, this study aimed to evaluate the effects of grape powder supplementation on inflammation and glutathione peroxidase levels in hemodialysis (HD) patients. Thirty-two HD patients from CIN, RJ, Brazil were studied and randomly into two groups: placebo group- PG (16 patients, 9 men, 52.7 ± 13.7 yrs) and experimental group EG (16 patients, 9 men, 53.0 ± 9.8 yrs). Each patient received 12g/day of powder grape with grape jelly or only grape jelly (placebo) during 5 weeks. The lipid profile, C-reactive protein (CRP) levels and glutathione peroxidase (GPx) activity were evaluated before and after supplementation (Table). The data suggest that the consumption of grape powder was effective to increase the activity of GPx and decreasing the progression the inflammation. Thus, our results indicate that grape powder plays an important role as an antioxidant agent in HD patients. Placebo Group Experimental Group Before After Before After CRP (mg/mL) 2.6±0.2 2.8±0.2* 2.6±0.2 2.6±0.2 LDL-C 86.3±38.8 94.4±34.3 80.5±25.0 82.9±22.1 Total cholesterol 154.6±44.9 163.3±44.8 143.9±29.2 145.4±28.3 GPx (U/g prot) 17.5±9.8 29.1±30.7 19.7±20.3 41.0±27.7* ⁎ p<0.05